2015
DOI: 10.1177/1479164115579799
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of elevated haemoglobin A1C among adolescent blood donors: Results from a voluntary screening programme including 31,546 adolescents

Abstract: More than 1 in 10 US adolescents have prediabetes or diabetes, and elevated glycosylated haemoglobin (HbA1C) in youth is associated with increased risk of death before the age of 55 years. We conducted a prospective, cross-sectional study of 31,546 consecutive volunteer blood donors, 16-19 years of age, who donated blood during school blood drives between 1 September 2011 and 21 December 2012 in Texas. In the overall cohort, the prevalence of elevated HbA1C was 11.5%, including 11.0% in the prediabetes range (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
(42 reference statements)
0
6
1
Order By: Relevance
“…12 However, some studies suggested that boys have higher glycemic levels than girls. 39 In our study, male sex was found to be associated with increased odds of having prediabetes only. Also, the prevalence of both prediabetes and T2DM were higher among younger adolescents.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…12 However, some studies suggested that boys have higher glycemic levels than girls. 39 In our study, male sex was found to be associated with increased odds of having prediabetes only. Also, the prevalence of both prediabetes and T2DM were higher among younger adolescents.…”
Section: Discussionmentioning
confidence: 41%
“…Most studies evaluating T2DM in youth showed that 65% to 70% of T2DM adolescents were females, usually from ethnic minorities . However, some studies suggested that boys have higher glycemic levels than girls . In our study, male sex was found to be associated with increased odds of having prediabetes only.…”
Section: Discussionmentioning
confidence: 99%
“…As a community health service, Oklahoma Blood Institute provides a fasting lipid panel as well as prostate specific antigen (PSA) screening for purchase with or without an associated blood donation [17]. Finally, Carter BloodCare has described their experience in implementing a regional HbA1c screening programme in a large adolescent blood donor population as a means to support public health [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, for countries with PLT production mainly based on apheresis, this may be important information in relationship to national epidemics concerning T2D. A study in Texas for instance, showed a prevalence of prediabetes and diabetes of 11% in a large cohort of donors of age 16–19 years . To establish a causal relationship of poor storage of PLT with (pre)diabetes and/or hypertriglyceridemia, further research is warranted.…”
Section: Discussionmentioning
confidence: 99%